Biografia św. Juliana z Toledo (642–690) w świetle krytycznej analizy źródeł - Kasprzak, Dariusz (Verbum Vitae, 2025)
In the case of Julian of Toledo, the Polish patristic bibliography confirms the existing trend in world patrology, namely the lack of any major interest both in the person of the author and in his work. Therefore, it seemed justified that a critical biography of the Bishop of Toledo should be written. The present study, after discussing the written sources and the state of research on Julian of Toledo, attempts, on their basis, to historically reconstruct his biography, highlighting two issues in particular: Julian’s Jewish origins and his probable involvement in the conspiracy against King Wamba. An analysis of 7th- and 8th-century sources on Julian of Toledo shows that his liturgical, canonical, and theological work confirms the validity of his royal appointments as bishop and archbishop of the Visigoth capital. Significant for the Church of the time were Bishop Julian’s initiatives to unify local Visigothic-Spanish liturgical rites, to codify canon law for the Visigothic Church, or to create a textbook lecture on purgatory. However, his participation in the conspiracy against King Wamba or in the creation of anti-Jewish legislation under King Erwig remains a matter that is difficult to assess.